Computational Evaluation of Bioactive Compounds from Bryophyllum pinnatum as a Novel GSK3B Inhibitor in Alzheimer's Disease - Babalola, Olorunfemi Oyewole; Ottu, Paul Olamide; Akinola, Olufemi Adebisi; Kehinde, Idayat Oyinkansola; Oluwatobiloba, Ayodeji Folasade; Oluwamodupe, Cecilia; Iwaloye, Opeyemi; Elekofehinti, Olusola Olalekan (Current Proteomics, 2024)
BackgroundGlycogen synthase kinase 3-beta (GSK3-β) is a protein that is linked to the formation of amyloid-beta (Aβ) plaques and neurofibrillary tangles, both of which are characteristic of Alzheimer's disease. The enzyme's hyperactivity phosphorylates tau proteins, forming neurofibrillary tangles that impair material transport between axons and dendrites and disrupt neuronal function. GSK3-β impacts amyloid precursor protein production, causing Aβ accumulation and neurodegeneration.Aim/ObjectiveThis study aimed to investigate the inhibitory mechanism of natural compounds from Bryophyllum pinnatum against GSK3-β.MethodsComputational approach, extra precision glide docking, and the Maestro molecular interface of Schrodinger suites were utilized to determine the binding free energy of the compounds against the prepared GSK3-β. The compounds' ADME parameters and Lipinski's rule of five were also evaluated. Using AutoQSAR, predictive models were constructed for both protein targets.ResultsThree hit compounds (kaempferol, quercetin, and 5,7,4'-trihydroxy-3,8-dimethoxyflavone) were found in this study. These compounds met the recommended range for the specified ADME parameters and passed the rule of five. Additionally, the hit compounds' predicted pIC50 values were promising.ConclusionOur study suggests that the investigated compounds can be used to design GSK3-β inhibitors.
Keywords: natural compounds